Displaced Legacies: Folded Time and Space for an Architecture of Becoming - Wei, Fang-Yun (Auckland University of Technology, 2010)
This research project is a hybrid between art and architecture; it sits in the realm of conceptual architecture, and is taken from the inspiration and practices between art and architecture; such as drawing, and photography. It is also inspired by the stories and spaces within my family. Specifically, it is about my grandfather’s fifty-year-old medical clinic, and his spatial practices that consist of repetition and resistances to change. There are two bodies. These bodies being the architectural as the medical clinic, and the human body as the divergent range of compressed lives exhibited across the multiple generations, hence the title of displaced legacies. The project seeks to bring these two bodies into proximity under a framework of medicalised bodies of thought. The medical is a pluralised body that works across a dialogue between beliefs and values inherent in Western and Eastern concepts of health. In this medicalised sense, life and death are crucial themes that play out within a concept of the uncanny. Under a medicalised body both an objective and subjective reality of bodily encounter is explored through the architectural figure and cross-generational rituals and beliefs. Significantly, the theme of the uncanny is a play within a play, or a doubling between dead spaces and spaces of the dead. The relations between dead space and the dead bodies, or hauntings of other generations, breathe a new complex living arrangement in my design. What is repressed uncannily makes room for a living on with new generations of thought within clinic building. The double effect of these bodies and spaces becomes an important spatial motif as a process of folding in the design project. The research question to come through in this spatial practice is how can conceptual design practices, that span a range of disciplinary approaches within medicine, art and architecture, respond adequately to the otherness of plural legacies? How do we approach the question of spatial design with a desire for respecting a plurality of heterogeneous histories residing together in the ever present?
Keywords: Legacies; Traditions; Photography; Fold